Tailored Light 1 High Power Lasers for Production - Poprawe, Reinhart (RWTHedition, 2018)
The Laser world consists basically of two areas, which are necessary and in many cases also sufficient for effective innovation: The right laser for the right application. For the individual application that means the determination of optimized process parameters in terms of laser power, peak power/ intensity, focus geometry and dimension, pulse length, pulse repetition rate and wavelength to name only the six most important ones. Once these parameters are identified, the corresponding Laser has to be selected on the basis of commercial availability. Obviously there is no such thing than "One Laser for all". The situation is rather comparable with electrical power, were depending on the demand of the application in terms of voltage, current and time corresponding power supplies need to be tailored, however, with the difference that in the case of the Laser the variety of parameters is even higher, thus the technology is more complex but on the other hand much more fl exible in terms optimizing the source to the application. As a consequence it is suggested to generate two volumes on Lasers and Applications named "Tailored Light".